The Composite Supercapacitor. Issue 4 (9th February 2016) - Fields, Richard; Lei, Chunhong; Markoulidis, Foivos; Lekakou, Constantina
Abstract: Inspired by the design of composite materials, we propose a new composite supercapacitor that comprises an integrated cell with high‐power‐ and high‐energy‐related electrode materials. The composite electrochemical double‐layer capacitor (EDLC) is the equivalent circuit of a high‐power EDLC of power P 1 and energy E 1 and a high‐energy EDLC of power P 2 and energy E 2 connected in parallel. A methodology is proposed and validated in this study for the design of an application‐specific composite supercapacitor of power P and energy E with P 1 / E 1 > P / E > P 2 / E 2 . The methodology was tested successfully in medium‐ and large‐sized application‐specific composite supercapacitors, which were fabricated in the form of pouch cells using an organic electrolyte. The application‐specific composite supercapacitors offered weight reductions of 40–60 % compared with supercapacitors based on the high‐power‐ or on high‐energy‐related electrode materials only. Abstract : Super Composite ! Inspired by the design of composite materials, we propose, design, and test a new composite supercapacitor. The supercapacitor comprises an integrated cell with high‐power‐ and high‐energy‐related electrode materials. The application‐specific composite supercapacitors offer weight reductions of 40–60 % compared with supercapacitors based on the high‐power‐ or high‐energy‐related electrode materials only.